Exploring patient attitudes to behaviour change before surgery to reduce peri‐operative risk: preferences for short‐ vs. long‐term behaviour change. (21st October 2019) - McDonald, S.; Yates, D.; Durrand, J. W.; Kothmann, E.; Sniehotta, F. F.; Habgood, A.; Colling, K.; Hollingsworth, A.; Danjoux, G.
Summary: Pre‐operative intervention to improve general health and readiness for surgery is known as prehabilitation. Modification of risk factors such as physical inactivity, smoking, hazardous alcohol consumption and an unhealthy weight can reduce the risk of peri‐operative morbidity and improve patient outcomes. Interventions may need to target multiple risk behaviours. The acceptability to patients is unclear. We explored motivation, confidence and priority for changing health behaviours before surgery for short‐term peri‐operative health benefits in comparison with long‐term general health benefits. A total of 299 participants at three UK hospital Trusts completed a structured questionnaire. We analysed participant baseline characteristics and risk behaviour profiles using independent sample t‐tests and odds ratios. Ratings of motivation, confidence and priority were analysed using paired sample t‐tests. We identified a substantial prevalence of risk behaviours in this surgical population, and clustering of multiple behaviours in 42.1% of participants. Levels of motivation, confidence and priority for increasing physical activity, weight management and reducing alcohol consumption were higher for peri‐operative vs. longer term benefits. There was no difference for smoking cessation, and participants reported lower confidence for achieving this compared with other behaviours. Participants were also more confident than motivated in reducing their alcohol consumption pre‐operatively. Overall, confidence ratings were lower than motivation levels in both the short‐ and long‐term. This study identifies both substantial patient desire to modify behaviours for peri‐operative benefit and the need for structured pre‐operative support. These results provide objective evidence in support of a 'pre‐operative teachable moment', and of patients' desire to change behaviours for health benefits in the short term.